The Multiple Meanings of Jatio Sangsad Bhaban - Bayezid Ismail Choudhury; Peter Armstrong (Journal of Social and Development Sciences, 2020)
Jatio Sangsad Bhaban, the National Assembly Building of Bangladesh, is an iconic building and architectural landmark designed by American architect Louis I. Kahn. Jatio Sangsad Bhaban was constructed between 1962 and 1983 and is located in the heart of Dhaka, the nation’s capital. The extant literature on Louis I. Kahn’s work suggests that Jatio Sangsad Bhaban is a significant architectural masterpiece. One of its most notable features is its architectonic quality, providing it with the grandeur of a modern monumental building. In this context, this paper aims to examine the underlying multiple meanings, that is, socio-political, cultural, historic and philosophical meanings of the Jatio Sangsad Bhaban building  By constructing and summarising meanings, rather than exploring the physical building itself, this paper supports the notion of multidimensional perspectives  of monumental architecture. —The multiple meanings of icoic architecture through  the lens of societal issues has been endorsed by many architectural critic. Accordingly, this paper considers the cultural, political, ethical and historical meanings of Jatio Sangsad Bhaban. Revealing and summarising other aspects apart from its architectonic dimensions is a new approach to understanding a widely acclaimed iconic building like Jatio Sangsad Bhaban